Elements of Style in Floral Arrangements: How Discerning Are Consumers Toward Floristry Design Principles and How Much Are They Willing to Pay? - Melinda Knuth; Vanessa Woods; Xuan (Jade) Wu; Charlie Hall; Marco Palma (HortScience, 2023)
Florists use design theory to create arrangements that they assume will be pleasing to consumers, thus increasing purchase rates and spending. However, certain elements of design theory and their relationship with consumer acceptance and spending have not been empirically tested. Using mixed logit models and eye-tracking technology, we investigated whether consumer preferences support three key elements of existing floral design theory: line, color, and form. We also examined consumer preferences for floral species, which, although not a traditional element of design theory, may influence consumer purchasing decisions. Our findings challenge existing design theory because consumers did not uniformly favor it. Instead, they valued symmetrical form, arrangements with similar (but not identical) colors, and, surprisingly, the presence of roses in an arrangement was the most crucial factor in capturing consumer attention and increasing the willingness to pay.